2020
DOI: 10.1002/vjch.2019000144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reaction temperature and reaction time on the structure and properties of MoS2 synthesized by hydrothermal method

Abstract: In this study, molybdenum disulfide (MoS2) nanostructures were synthesized by a facile hydrothermal process, using ammonium heptamolybdate tetrahydrate ((NH4)6Mo7O24.4H2O) and thiourea (CH4N2S) as the reactants. The effects of experimental parameters including reaction temperatures and reaction times on the structure and morphology of MoS2 have primarily been investigated. The morphology, microstructure, chemical composition and optical properties of as‐synthesized MoS2 were characterized using field emission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…The diffraction peaks are observed at 14.26, 32.66, 35.84, 39.51, 44.36, 49.87, and 58.07° for the corresponding hkl planes of <002>, <100>, <102>, <103>, <006>, <105>, and <110>, which are similar to the standard JCPDS card number 37–1492 with a hexagonal crystal system. Since the dopant effect is minimum, there is no obvious shift in the peaks and additional peaks observed except for the intensity variation …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diffraction peaks are observed at 14.26, 32.66, 35.84, 39.51, 44.36, 49.87, and 58.07° for the corresponding hkl planes of <002>, <100>, <102>, <103>, <006>, <105>, and <110>, which are similar to the standard JCPDS card number 37–1492 with a hexagonal crystal system. Since the dopant effect is minimum, there is no obvious shift in the peaks and additional peaks observed except for the intensity variation …”
Section: Resultsmentioning
confidence: 99%
“…Since the dopant effect is minimum, there is no obvious shift in the peaks and additional peaks observed except for the intensity variation. 24 Raman spectroscopy is a potential technique used to identify the structural fingerprint (characteristic vibrational, rotational, and other low-frequency modes) and the influences of doping on the perturbation of the crystal lattice for pure-MoS 2 , Nd-, and Gd-doped MoS 2 samples. There are six vibrational modes observed at 174.44, 275.59, 367.44, 404.25, 822.61, and 988.09 cm −1 (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…The two emission peaks at 670 (A) and 640 nm (B) correspond to the direct transition of A and B excitons, corresponding to A and B processes in Figure c,d i , respectively. The A peak is the direct transition of A excitons between the K point of VB top and the K point of CB bottom, whereas the B peak is the direct transition between CB and lower VB; the energy difference between peaks A and B is attributed to the VB splitting due to the strong spin-orbital interaction. , The accompanying emission peaks at 745 and 780 nm correspond to the first-order and second-order phonon companion lines, respectively. Additionally, the I peak at 810 nm (Figure b) originates from the indirect band gap transition between Γ and K points and appears at a lower wavelength of PL image.…”
Section: Resultsmentioning
confidence: 99%
“…Xuan et al found that the reaction time significantly contributes to the restacking of the MoS 2 crystal structure. 145 The significant advantages of these methods are that they use a cheap and abundant sulfur source and produce material of high crystallinity and larger surface area. However, control of the directional growth of MoS 2 layers is difficult in the hydrothermal method; also, the structure is prone to aggregation, and therefore the utilization of surfactants like cetyltrimethylammonium bromide (CTAB) to control the particle shapes 146 is necessary.…”
Section: Physical Chemical Properties and Mosmentioning
confidence: 99%
“…The variation in temperature, pressure, and microwave power (in some cases) can control the morphology, conductivity, microstructure, and composition of the synthesized MoS 2 , which controls the final nature of the as-synthesized MoS 2 . Xuan et al found that the reaction time significantly contributes to the restacking of the MoS 2 crystal structure . The significant advantages of these methods are that they use a cheap and abundant sulfur source and produce material of high crystallinity and larger surface area.…”
Section: Physical Chemical Properties and Mos2 Synthesis Techniquesmentioning
confidence: 99%